Monogenic Diabetes Modeling: In Vitro Pancreatic Differentiation From Human Pluripotent Stem Cells Gains Momentum - Burgos, Juan Ignacio; Vallier, Ludovic; Rodríguez-Seguí, Santiago A. (Frontiers in Endocrinology, 2021)
The occurrence of diabetes mellitus is characterized by pancreatic β cell loss and chronic hyperglycemia. While Type 1 and Type 2 diabetes are the most common types, rarer forms involve mutations affecting a single gene. This characteristic has made monogenic diabetes an interesting disease group to model in vitro using human Pluripotent Stem Cells (hPSCs). By altering the genotype of the original hPSCs, or by deriving human induced Pluripotent Stem Cells (hiPSCs) from patients with monogenic diabetes, changes in the outcome of the in vitro differentiation protocol can be analyzed in detail to infer the regulatory mechanisms affected by the disease-associated genes. This approach has been so far applied to a diversity of genes/diseases and uncovered new mechanisms. The focus of the present review is to discuss the latest findings obtained by modeling monogenic diabetes using hPSC-derived pancreatic cells generated in vitro. We will specifically focus on the interpretation of these studies, the advantages and limitations of these models, and the future perspectives for improvement.